Comparative statics for a consumer with possibly multiple optimum consumption bundles - Indraneel Dasgupta; Prasanta K. Pattanaik (Institute for the Study of Labor (IZA), 2010)
Non-positivity of the generalized substitution effect, non-positivity of the own-price substitution effect, homogeneity of degree zero in all prices and income, and the law of demand are some of the most primitive comparative static results in the standard revealed preference theory of consumers' behaviour. These results are however derived for demand functions. The literature does not have corresponding comparative static results for the more plausible case of demand correspondences, where the consumer is permitted to have multiple chosen bundles in a given price-income situation. Using the revealed preference approach to the theory of consumers' behaviour, this note establishes such results for demand correspondences; the analysis can be readily adapted to prove corresponding results in the preference-based approach.
Keywords: D11; 330; Demand correspondence; weak axiom of revealed preference; non-positivity of generalized substitution effect; non-positivity of own-price substitution effect; homogeneity of degree zero; law of demand; Konsumtheorie; Offenbarte Präferenzen; Produktsubstitution; Substitutionseffekt; Theorie